Relationship of age with periodontal diseases for males and females in Bangladesh; A hospital registry based cross-sectional observational study. - Khan, Md Huzzatul Islam; Sadia, Ruksana Islam; Ema, Sumaia Akter; Shahabuddin, Nayna Binte; Rahman, Rifat; Iqbal, Md Ashif (Update Dental College Journal, 2019)
Periodontal diseases are the most commonly occurred diseases in the oral cavity with a widespread distribution around the globe. Variation in periodontal tissues associated with the aging and gender of the patient. The aim of this study was to determine relationship of age with periodontal diseases for males and females in Bangladeshi people. This study was conducted on 1837 patients visiting Department of Periodontology & Oral Medicine, Update Dental College & Hospital, from January 2017 to December 2018 (2 years) through a non-interventional cross-sectional method using descriptive and analytical statistics. Periodontal disease is the dependent variable of this study; patient age and gender serve as the independent variable. Total 37.5 % patients suffered from periodontitis and 62.5% suffered from gingivitis. Up to 48 years of age the prevalence of gingivitis was higher (70.64%) but periodontitis was more common (64.76%) in case of people over 48 years age. There is a significant (p<0.05) correlation between age and periodontal diseases exists in this study but no significant (p>0.05) correlation identified with gender. Distribution of periodontal diseases shows similar pattern between female (gingivitis=62.61%, periodontitis=37.53%) and male (gingivitis=62.47%, periodontitis=37.39%).Periodontal diseases are primarily correlating with the age but gender may not be associated. The most prevalent form of periodontal disease is gingivitis. Update Dent. Coll. j: 2019; 9 (2): 13-16